2020
DOI: 10.1155/2020/5691974
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Histopathological and Immunohistochemical Study of Ruminant’s Cutaneous Papillomavirus in Iraq

Abstract: e papilloma viruses are constituted of double-stranded DNA and are a more common lesion in ruminant's skin in Iraq. e p53 tumor suppressor protein reveals an essential role in cell cycle control. is study intends to investigate the clinical, histopathological, and immunohistochemical features of cutaneous papilloma in ruminants in Iraq. Samples had been collected from a total of 10 animals (three cattle, three goats, and four sheep) with multiple papillomatosis lesions. e samples were processed for histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
4
14
1
Order By: Relevance
“…On clinical examination, the mass distribution of both Angus and limousin cattle patients did not differ from the results reported by Mansour et al [13], which states that there are papillomas in the shoulder, head and neck area. However, it is different from the report of Al-Salihi et al [14], papillomas in cattle aged 5 months to 5 years were found in all parts of the animal body. BPV infection, depending on the viral pathotype and environmental factors, causes clinical signs in cattle, such as skin fibropapilloma caused by BPV-1 and 2, upper gastrointestinal cancer caused by BPV-4, papillomatosis of the nipple and udder caused by BPV-1, -5, -6, -9 and -10, penis papillomatosis caused by BPV-1, bladder cancer caused by BPV-1 and 2 and skin papilloma caused by BPV-8 [15,16].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…On clinical examination, the mass distribution of both Angus and limousin cattle patients did not differ from the results reported by Mansour et al [13], which states that there are papillomas in the shoulder, head and neck area. However, it is different from the report of Al-Salihi et al [14], papillomas in cattle aged 5 months to 5 years were found in all parts of the animal body. BPV infection, depending on the viral pathotype and environmental factors, causes clinical signs in cattle, such as skin fibropapilloma caused by BPV-1 and 2, upper gastrointestinal cancer caused by BPV-4, papillomatosis of the nipple and udder caused by BPV-1, -5, -6, -9 and -10, penis papillomatosis caused by BPV-1, bladder cancer caused by BPV-1 and 2 and skin papilloma caused by BPV-8 [15,16].…”
Section: Discussioncontrasting
confidence: 95%
“…Intranuclear inclusions in this study were found to be few. The same is the case with previous studies by Al-Salihi et al and Tan [14,10]. According to Ozsoy et al [11], found inclusion bodies in basal cells.…”
Section: Advances In Biological Sciences Research Volume 12supporting
confidence: 90%
“…In accordance with the findings of the literature (Atasever et al 2005;Özsoy et al 2011;Carvalho et al 2013;Hong and Kim 2015;Rojas Anaya et al 2016;Beytut 2017;Hamad et al 2017), in this study, a cauliflower-like wartlike growth with or without a stem was detected on the skin of animals with papillomas and fibropapillomas. Hyperkeratosis (Atasever et al 2005;Hong and Kim 2015;Branci et al 2020), acanthosis (Özsoy et al 2011, Araldi et al 2015Al-Salihi et al 2020), rete pegs (Beytut et al 2017Hamad et al 2017;Ata et al 2018), koilocytosis (Carvalho et al 2013Araldi et al 2014;Hamad et al 2017), degeneration in keratinocytes (Atasever et al 2005;Tozato et al 2013;Timurkan and Alcigir 2017), keratohyaline granules (da Silva et al2015;Beytut et al2017, Timurkan and Alcigir 2017), dermal proliferation (Grindatto et al 2015Hamad et al 2016;Yamashita-Kawanishi et al 2019), the histopathological changes observed in papillomas and fibropapillomas were also recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These viruses show an affinity for mucosal tissues and squamous epithelial as well as mesenchymal tissue (Araldi et al 2014;Hamad et al 2016). Although these viruses show tropism to the squamous epithelium of warm-blooded animals, particulary cattle, cross-species infection has been reported only in horses and other equines (AL-Salihi et al 2020). BPV, which is highly species specific and has been detected in water buffaloes, bison, giraffes, zebras, antelopes, yak, horses, donkeys, tapirs, and other species (da Silva et al 2015;Rojas-Anaya et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, papilloma (also called warts), are most commonly found on the head, neck shoulder and occasionally on the back and abdomen. The lesions also have a keratotic surface due to epidermal proliferation that resembles a cauliflower (AL-Salihi et al 2020); Timurkan and Alcigir 2017). Warts or papilloma would appear like a cauliflower, dry and rough in appearance.…”
Section: Introductionmentioning
confidence: 99%